Data donation and data altruism to face algorithmic bias for an inclusive digital healthcare (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This paper addresses the issue of algorithmic bias in the medical field and the need to regulate data donation. Although bias and discrimination in health care are not only related to the use of algorithms but have long-standing origins and heterogeneous causes, the use of artificial intelligence could exacerbate such biases by making them structural and difficult to identify. In many cases, the presence of algorithmic bias is due to incomplete or unrepresentative datasets and the difficulty for researchers to access the data. Data donation could be a useful tool to face this phenomenon, increasing the individual’s sovereignty over his or her personal data sphere and enabling an individual’s participation in scientific and technological progress from a solidarity perspective.
Keywords: Artificial intelligence; algorithmic bias; data donation; data altruism; healthcare